Redescription of Moenkhausia melogramma (Characiformes: Characidae), a poorly known tetra from the western Amazon basin - Soares, Isabel M. [UNESP]; Ota, Rafaela P.; Lima, Flavio C. T.; Benine, Ricardo C. [UNESP] (Soc Brasileira Ictiologia, 2020)
Moenkhausia melogramma is herein redescribed, based on the examination of the holotype plus additional specimens from the western Amazon basin in Brazil, Colombia, Peru, and Ecuador. Moenkhausia melogramma shares with M. collettii, M. conspicua, M. copei, M. venerei, and M. flava a broad dark longitudinal stripe across the eye, and a well-defined dark stripe on the anal-fin base. It can be promptly distinguished from these species by having two humeral blotches. Additionally, we provide comments on the putative relationships of Moenkhausia melogramma with the aforementioned congeners and the Hemigrammus lunatus species-group.
Keywords: Bony hooks; Color pattern; Hemigrammus machadoi; Moenkhausia collettii species-group; Taxonomy